Attacking styles of play in football: a comparison between UEFA Champions League and Copa Libertadores da América - Romero Clavijo, F. A.; Amancio Silva, E. H.; Flôres, F.; Cesar Corrêa, U.; Drews, R. (International Journal of Performance Analysis in Sport, 2025)
This investigation aimed to compare the attacking styles of play (ASPs) between participants in the UEFA Champions League (UCL) and Copa Libertadores de América (CLA). 224 matches from the round of 16 to the semi-finals were analysed, including UEFA Champions League (n = 112, seasons 2017-2019 and 2020-2022) and Copa Libertadores (n = 112, seasons 2019-2022), comprising 31 teams from UCL and 37 teams from CLA. Nine key attacking performance indicators related to ball possession, corner kicks, shots on goal, and goals scored were collected. Hierarchical cluster analysis was performed to distinguish different ASPs, and an association measure was used to identify the key performance indicators that differentiate these styles. UCL teams exhibited a broader range of ASPs compared to CLA teams, demonstrating greater variability. Ball possession indicators were found to be significant in differentiating the ASPs. UCL teams showed a preferred ASP while also employing other styles to diversify their attacking behaviour. In contrast, CLA teams favoured two preferred ASPs, a pattern that became more pronounced as the tournaments progressed. In conclusion, European and South American teams display differences in both the quantity and preference for attacking styles across different phases of their respective continental competitions.